What is the Best Location of a Smart Airport in Juarez, Mexico? - Reyes, Aida Yarira (Springer International Publishing, 2021)
Location of airports is a key factor for the sustainable and competitive development of the smart cities. Airport location projects influence many aspects, such as: growth of the city, manoeuvres of airlines, transport of passengers, and soil preservation. They also bring a variety of social, environmental and economic benefits. The location of an airport that comply with land use and airspace rules and regulations is of utmost importance. This paper presents the problem of: What is the best location of an airport in Ciudad Juarez? The designed a multi-criteria analysis approach to locate a new smart airport in a border area of Northern Mexico. The study bases on the model of indicators for the competitiveness of the city and inter-national regulations for locating airports in border areas. The study also bases on the medium smart airport model and considers four location alternatives: two to the Northwest (1) and (2), one to the Southeast (3) and the fourth in the South (4). We used TOPSIS multi-criteria model to obtain the best alternative to allow for the most convenient location. The analysis resulted in alternative 2, located to the northwest, being the best, followed by location 1 and location 4.